2020
DOI: 10.1098/rstb.2019.0747
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of gross primary productivity to climatic drivers during the summer drought of 2018 in Europe

Abstract: In summer 2018, Europe experienced a record drought, but it remains unknown how the drought affected ecosystem carbon dynamics. Using observations from 34 eddy covariance sites in different biomes across Europe, we studied the sensitivity of gross primary productivity (GPP) to environmental drivers during the summer drought of 2018 versus the reference summer of 2016. We found a greater drought-induced decline of summer GPP in grasslands (−38%) than in forests (−10%), which coincided with reduced evapotranspir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 54 publications
4
63
0
1
Order By: Relevance
“…In a Dutch case study authors found a NECB of 20.1 t CO 2 ha −1 yr −1 average over the years -2008(Schrier-Uijl et al, 2014. Comparing GPP and R eco estimates with earlier reports we find that GPP of the sites was higher than values found by Tiemeyer et al (2016) for productive and drained peatlands (−70 ± 18 t CO 2 ha −1 yr −1 ), especially in the year 2017 (−88.7 ± 7.2 t CO 2 ha −1 yr −1 ), and falls back to the range in 2018 (−69.0 ± 8.9 t CO 2 ha −1 yr −1 ) due to the droughtinduced decline of CO 2 uptake (Fu et al, 2020). Higher GPP estimates seem reasonable given the high C export in 2017 (on average 18.0 t CO 2 ha −1 ), which was substantially larger than the 8.5 t CO 2 ha −1 reported by Tiemeyer et al (2016) for grassland on organic soils.…”
Section: Reasonably High Neementioning
confidence: 55%
See 1 more Smart Citation
“…In a Dutch case study authors found a NECB of 20.1 t CO 2 ha −1 yr −1 average over the years -2008(Schrier-Uijl et al, 2014. Comparing GPP and R eco estimates with earlier reports we find that GPP of the sites was higher than values found by Tiemeyer et al (2016) for productive and drained peatlands (−70 ± 18 t CO 2 ha −1 yr −1 ), especially in the year 2017 (−88.7 ± 7.2 t CO 2 ha −1 yr −1 ), and falls back to the range in 2018 (−69.0 ± 8.9 t CO 2 ha −1 yr −1 ) due to the droughtinduced decline of CO 2 uptake (Fu et al, 2020). Higher GPP estimates seem reasonable given the high C export in 2017 (on average 18.0 t CO 2 ha −1 ), which was substantially larger than the 8.5 t CO 2 ha −1 reported by Tiemeyer et al (2016) for grassland on organic soils.…”
Section: Reasonably High Neementioning
confidence: 55%
“…
Peatlands cover only 3 % of the land and freshwater surface of the planet, yet they contain one-third of the total carbon (C) stored in soils (Joosten and Clarke, 2002). Natural peatlands capture C by producing more organic material than decomposed due to waterlogged conditions (Gorham et al, 2012;Lamers et al, 2015). Drainage of peatlands for agricultural purposes leads to aerobic oxidation of organic material and increased gas exchange releasing CO 2 and N 2 O at high rates (
…”
mentioning
confidence: 99%
“…Such differences may be due to differences across DGVMs and FLUX-COM in the storage capacity of moisture within the soil. Fu et al [43] indicated that extreme drought affected the magnitude of the sensitivity of GPP from EC measurements to climate conditions, particularly SM, but the change in the sensitivity of productivity to drought was partly dependent on ecosystem type. Consistent with their results, FLUXCOM reports generally higher sensitivity of GPP to SM and more negative sensitivity to T at continental scale during the DH events as compared to other years (electronic supplementary material, figure S6).…”
Section: Discussionmentioning
confidence: 99%
“…In situ measurements, remote sensing and data-driven and process models support a dominant role of gross primary productivity (GPP) decrease, rather than a terrestrial ecosystem respiration (TER) increase, to most of the negative CO 2 uptake anomalies seen by inversions [33,42], although variability between sites is found [44,46,47]. As in previous extreme summers, the productivity of crops and grasslands was more strongly affected by the summer drought in 2018 than forests exposed to the effects of both high soil moisture deficits and high water vapour pressure deficits [33,[47][48][49], even though some forests also registered stomatal closure and reduced GPP, especially those at lower altitudes [48] and more exposed to drought [44]. Wetlands in Scandinavia were also negatively affected by the drought [50], but floodplains in the Czech Republic registered higher than average productivity [43].…”
Section: Ecological Perspectivementioning
confidence: 99%
“…Nevertheless, different responses to the summer drought are found for similar ecosystem types and even for the same species. In situ-based studies [44,[47][48][49] report reductions of 40-60% in evapotranspiration and/or stomatal conductance for droughtaffected eddy-covariance sites in response to high vapour pressure deficit, explaining GPP reductions and increased water-use efficiency. But Lindroth et al [44] show that forest ecosystems in Scandinavia were generally able to cope well with the strong drought by accessing deeper water layers, and therefore maintain close to average evaporation rates in spite of drought.…”
Section: Ecological Perspectivementioning
confidence: 99%